العلاقة بين قلق المستقبل و كل من معنى الحياة و الوحدة النفسية و الاكتئاب و مفهوم الذات لدى السيدات العقيمات - عبدالعزيز، نادية محمود غنيم (جامعة الأزهر - كلية التربية, 2012)
هدفت الدراسة الحالية إلى معرفة العلاقة بين قلق المستقبل وبعض المتغيرات النفسية المرتبطة به، والمتمثلة في (معنى الحياة- الوحدة النفسية- الاكتئاب- مفهوم الذات) لدى عينة من السيدات اللاتي تعاني العقم، وتكونت عينة الدراسة من (150 سيدة) تراوحت أعمارهن من (30- 45) سنة، وتم تطبيق الأدوات الآتية (قلق المستقبل- معنى الحياة- الوحدة النفسية- الاكتئاب- مفهوم الذات) من إعداد الباحثة، وقد توصلت النتائج إلى وجود علاقة ارتباطية سالبة ودالة إحصائياً بين قلق المستقبل ومعنى الحياة، وبين قلق المستقبل ومفهوم الذات، كما وجدت علاقة ارتباطية موجبة ودالة إحصائيا بين قلق المستقبل والاكتئاب، وبين قلق المستقبل والوحدة النفسية، كما أمكن التنبؤ بقلق المستقبل من خلال الاكتئاب ومعنى الحياة، ومفهوم الذات، والوحدة النفسية على الترتيب The purpose of this study was to investigate the relationship between the future Anxiety and the concern of some psychological variables associated with it, and of (the meaning of life-Loneliness- Depression - self-concept) in a sample of women who suffered from infertility, and the sample of the study consisted of (150 Lady suffer from sterility) between the ages of (30-45 years), was applied following tools (concern the future Anxiety-the meaning of life -loneliness - Depression-self-concept) prepared by the researcher ,the results shows to the significant correlation negative relationship between the future anxiety and the meaning of life, and the concern the future anxiety and self- concept, as found a positive and statistically significant correlation between the future anxiety and depression, and the future anxiety and loneliness, also possible to predict the future with concern through the depression and the meaning of life and self-concept and loneliness.
789645
Keywords: العقم -- المرأة -- الصحة النفسية -- مفهوم الذات -- الإرشاد النفسي